A qualitative study of barriers to and facilitators of optimal engagement in care among PLWH and substance use/misuse. (December 2016) - Kuchinad, Kamini; Hutton, Heidi; Monroe, Anne; Anderson, Garrick; Moore, Richard; Chander, Geetanjali
Abstract Background Persons living with HIV (PLWH) and substance use/misuse experience significant barriers to engagement in HIV care at every step of the HIV care continuum including: (1) HIV testing and diagnosis (2) linkage to clinical care (3) retention in care pre-antiretroviral therapy (ART) (4) ART initiation and adherence (5) viral suppression. We qualitatively explored the facilitators of and barriers to participation in the HIV care continuum among PLWH with substance use/misuse. Methods We performed semi-structured in-depth interviews with 34 PLWH in care with recent substance use. The transcripts were analyzed in an iterative process using an editing style analysis. Interviews were conducted until thematic saturation was achieved. Results Participants attributed an escalation in drug use at the time of diagnosis to denial of their disease and the belief that their death was inevitable and cited this as a barrier to treatment entry. In contrast, participants reported that experiencing adverse physical effects of uncontrolled HIV infection motivated them to enroll in care. Reported barriers to retention and adherence to care included forgetting medications and appointments because of drug use, prioritizing drug use over HIV treatment and side effects associated with medications. Participants described that progression of illness, development of a medication taking ritual and a positive provider-patient relationship all facilitated engagement and reengagement in care. Conclusions PLWH with substance use engaged in care describe barriers to and facilitators of optimal engagement related to and distinct from substance use. Greater understanding of the biologic, psychological and social factors that promote and impair engagement in care can inform interventions and reduce the increased morbidity and mortality experienced by PLWH with substance use.